A Comparative Investigation of the Impact of Two Different Charcoal Stove Configurations on Polycyclic Aromatic Hydrocarbons and Particulate Matter Emissions (Journal of Energy and Safety Technology (JEST), 2022)
Due to dwindling income occasioned by inflation, vast numbers of Nigerians have reverted to charcoal stoves to meet or supplement their domestic energy need. Two brands of charcoal stoves (local and modernized) presently in use in Nigeria were investigated for their contributions to indoor level of polycyclic aromatic hydrocarbons (PAHs). The two stoves were loaded with equal quantity of wood charcoals and allowed to burn for 2-hours a day in separate rooms of equal sizes. Passive sampling involving the use of polyurethane foam (PUF) disks was adopted and the PUF disks were withdrawn after 3 and 7 days for laboratory analysis. Gas Chromatography – Mass Spectrometer (GC-MS) analytical procedures were used for the determination of the PAHs concentrated on the PUF disks. The total PAH concentrations after 3 days were 1.74 μg/m3 and 0.61 μg/m3 for local and modern charcoal stoves respectively while their corresponding total concentrations after 7 days were 2.91 μg/m3 and 2.01 μg/m3. The modern charcoal stove showed better performances over the two durations. However, the total PAHs concentrations from both stoves exceeded the ambient air recommended limits. Giving the carcinogenic tendencies of some of the PAHs, the study concluded that none of the two stoves is safe for indoor application.
Keywords: Charcoal; Charcoal stove; PAHs; Particulates; Passive Sampling; Indoor Air